REALIZING GOOD GOVERNANCE IN IMPROVING THE QUALITY OF PUBLIC SERVICES - Fauziyah, Nina; Febrianti, Andini Alifa (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
Governance is a conceptual framework that includes public philosophy and management. Good governance emphasizes the principles of accountability, transparency, excellent service, democracy, participation, efficiency, and the rule of law. However, currently there are many public services that are efficient in serving the community, therefore it is necessary to improve good governance. This research method uses a qualitative literature study to understand Good Governance in Public Services. The results show that to create good governance, it requires the involvement of all stakeholders. In addition, the existence of responsive public services and the ability to adjust to the needs of the community are the main keys in achieving effective and sustainable governance.